If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + y = -27 Solving 4x + y = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 4x + y + -1y = -27 + -1y Combine like terms: y + -1y = 0 4x + 0 = -27 + -1y 4x = -27 + -1y Divide each side by '4'. x = -6.75 + -0.25y Simplifying x = -6.75 + -0.25y
| 4sen^2(x)-8sen(x)-5=0 | | y+8=0.1(x-3) | | 172n=184 | | y-1=0.2(x+3) | | y+4=10(x-3) | | 361n=130 | | 4-(2x-11)= | | 130n=361 | | 575n=980 | | 361n=172 | | 2(v-3)=9v+36 | | 8u+32+3u=-23 | | 2x=5(2-4x) | | 1/sinh(x) | | ln(x^2-25)=10+ln(75) | | X^5/15×X^7/15 | | 3(a+2)+2(4+b)= | | (k-1)x^2-2kx+k^2=0 | | -2v+8(v-3)=-6 | | (k+1)x^2-2kx+k^2=0 | | 7+2x=8-5(3+x) | | 7x+7x+6b= | | 6+w=-12+2w | | -3(y+6)=-45 | | 8a-2b+4-3b+a-3= | | y-9=0.3(x+2) | | 4cos^2x-4cosx-3=3 | | -9x(x+6)=3(x+18) | | a+c=b+c | | -10n+10=-12n | | y-9=0.3(x+9) | | y-7=-3(x-1) |